Perlindungan Hukum terhadap Masyarakat Akibat Penggunaan Knalpot yang Tidak Memenuhi Standar Teknis yang Berdampak pada Lingkungan dan Ketenteraman Umum - Pahriah Gustina Ayu; Triyana Syahfitri; Syariffuddin (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the implementation of legal protection for the community against the impacts of using exhaust systems that do not comply with technical standards on the environment and public order in Tembilahan, and to identify the factors hindering its implementation. This empirical legal research employed a qualitative approach using primary data from interviews and observations, supported by secondary data from legislation and relevant literature. The findings show that legal protection has been implemented through preventive measures, including legal awareness campaigns and traffic safety education, as well as repressive measures such as traffic inspections, law enforcement, and sanctions against violators. However, its implementation remains suboptimal due to low public legal awareness, limited law enforcement supervision, inadequate inter-agency coordination, and the continued circulation of non-compliant exhaust systems. Strengthening collaboration among law enforcement agencies, local government, and the community is therefore essential to improve legal protection and promote a safe, orderly, and environmentally sustainable society.